1715-55 N.C. Sess. Laws 36, An Additional Act to an Act for Appointing Toll-Books, and for Preventing People from Driving Horses, Cattle, or Hogs to Other Persons’ Lands, ch. 5, § 7 - (:unkn) unknown (General Publisher, 1729)
Prohibited “slaves” to hunt on any person’s land besides their master’s w ith any weapon.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES